2015
DOI: 10.3390/ijerph120201998
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index (BMI) Is Associated with Microalbuminuria in Chinese Hypertensive Patients

Abstract: There is no general consensus on possible factors associated with microalbuminuria in hypertensive patients nor any reported study about this issue in Chinese patients. To examine this issues, 944 hypertensive patients were enrolled in a study based on a cross-sectional survey conducted in Southern China. Multivariate regression analyses were performed to identify the factors related with the presence of microalbuminuria and urinary excretion of albumin. The prevalence of microalbuminuria in hypertensive and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
1
15
1
Order By: Relevance
“…Thus, this finding implies that obese people have the higher likelihood for the development of microalbuminuira than others. Additionally, this finding is supported by previous studies reporting the positive relationship between the obesity and microalbuminuria [7][8][9]. Especially, recent body of evidence focused the significant relationship between microalbuminuria and central or visceral obesity.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Thus, this finding implies that obese people have the higher likelihood for the development of microalbuminuira than others. Additionally, this finding is supported by previous studies reporting the positive relationship between the obesity and microalbuminuria [7][8][9]. Especially, recent body of evidence focused the significant relationship between microalbuminuria and central or visceral obesity.…”
Section: Discussionsupporting
confidence: 84%
“…Microalbuminuria, defined as a urinary albumin-to-creatinine (UACR) ranging within 30-300 mg/g, is usually used in evaluating and managing diabetic nephropathy [5,6]. Body of evidence indicated that obesity was deeply associated with diabetic nephropathy manifested by microalbuminuria [7][8][9]. Additionally, even in non-diabetic patients, risk for microalbuminuria was related with the degree of obesity [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…ST segment elevation MI cases were not included in their study 14 . Association of microalbuminuria with dyslipidemia and obesity was not significant in our study; however few studies have shown significant association 6,[15][16][17][18] . 98 out of 100 ACS patients in our study were having one or more risk factors.…”
contrasting
confidence: 85%
“…Albuminuria can easily be assessed as albumin‐creatinine ratio (ACR) in urine samples even in simple clinical settings. Risk markers associated with presence of albuminuria in Caucasians and Asians with hypertension include age, diabetes mellitus (DM), obesity, smoking, and insufficient blood pressure (BP) control . Knowledge on risk markers suggesting presence of albuminuria among patients with hypertension in sub‐Saharan Africa (SSA) has only been investigated in urban areas and is, in general, comparable with those of the Western world .…”
mentioning
confidence: 99%
“…Risk markers associated with presence of albuminuria in Caucasians and Asians with hypertension include age, diabetes mellitus (DM), obesity, smoking, and insufficient blood pressure (BP) control. 3,4 Knowledge on risk markers suggesting presence of albuminuria among patients with hypertension in sub-Saharan Africa (SSA) has only been investigated in urban areas and is, in general, comparable with those of the Western world. 5,6 The lifestyle and living conditions in rural areas of SSA differ from urban environments in terms of physical activity, nutrition, and patterns of cardiovascular disease.…”
mentioning
confidence: 99%